E-learning courseware for language education in Japan: its application and student perceptions. (4th May 2018) - Hirata, Yoko
Abstract: Commercial e-learning courseware for English education has been widely used in Japanese universities as an effective tool to assist students in improving their overall English skills. The courseware that is described in this paper is believed to be useful for teachers to assess students' progress and evaluate their dedication to English study. Despite the fact that various remarkable technical features have been discussed, not much research has been done to investigate student evaluation of courseware. This paper outlines a study carried out to investigate how Japanese undergraduate students rate commercial online courseware for their English study and what the relationship is between their appreciation of courseware and their educational background. The findings suggest that although different students exhibit different preferences there is a close relationship between the benefits of courseware and their previous language-learning experiences.